MANAGEMENT OF DIGITALIZATION OF MARKETING AUDIT AND ITS FINANCIAL SUPPORT - LIKHONOSOVA, Ganna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In today’s digital business transformation environment, marketing audit is becoming an important strategic management tool that allows assessing the effectiveness of marketing campaigns, optimizing advertising costs, and increasing the competitiveness of companies. However, traditional approaches to marketing audit do not meet the challenges of the digital economy, as they are based on outdated analysis methods and do not take into account the opportunities provided by Big Data, artificial intelligence (AI), blockchain, CRM systems, and automated analytical platforms. The study examines conceptual approaches to the digitalization of marketing audit, identifies key technological solutions (AI, Big Data, CRM systems, IoT, blockchain), and analyzes their impact on the effectiveness of marketing analytics. A financial and economic model for assessing the effectiveness of marketing audit digitalization is proposed, which is based on ROI (Return on Investment), CBA (Cost-Benefit Analysis), Payback Period (PP), and NPV (Net Present Value) indicators. Practical cases of the implementation of digital technologies in marketing audit by leading companies, in particular Coca-Cola, Amazon, PepsiCo, Netflix, demonstrating the positive impact of digital transformation on marketing efficiency and cost reduction, are considered. The originality of the study lies in the comprehensive analysis of the relationship between digital technologies, financial support and marketing efficiency. The scientific novelty of the work includes the systematization of approaches to the digitalization of marketing audit taking into account modern technological trends and the proposal of practical mechanisms for financial management of digital marketing solutions for enterprises of various scales. The practical significance of the study lies in the possibility of using the results obtained as a basis for developing corporate strategies for digital marketing audit, as well as as analytical material for companies implementing digital technologies in their marketing activities.